2022
DOI: 10.1111/jam.15505
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbiota from Mexican patients with metabolic syndrome and HIV infection: An inflammatory profile

Abstract: Aim A remarkable increase in metabolic syndrome (MetS) has occurred in HIV‐infected subjects. Gut dysbiosis is involved in the pathogenesis of metabolic disorders. Therefore, the aim is to explore the profile of the gut microbiota in Mexican population with HIV infection and MetS. Methods and Results In all, 30 HIV‐infected patients with MetS were compared to a group of 30 patients without MetS, treated with integrase inhibitors and undetectable viral load were included in the study. Stool samples were analyse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 79 publications
2
16
0
Order By: Relevance
“…Thus, it was meaningful to study obesity separately from MS, which allowed the researchers to obtain some new microbial biomarkers. Notably, the partially altered genera in our study were also consistent with the results of studies that analyzed other metabolic diseases ( 28 30 ). These findings indicated that gut dysbiosis existed in children with MS ( 31 ).…”
Section: Discussionsupporting
confidence: 91%
“…Thus, it was meaningful to study obesity separately from MS, which allowed the researchers to obtain some new microbial biomarkers. Notably, the partially altered genera in our study were also consistent with the results of studies that analyzed other metabolic diseases ( 28 30 ). These findings indicated that gut dysbiosis existed in children with MS ( 31 ).…”
Section: Discussionsupporting
confidence: 91%
“…Metabolic syndrome (MetS), characterized by decreased glucose tolerance and increased insulin resistance, is gaining importance due to increased prevalence and earlier presentation in the HIV-positive population, predisposing them to cardiovascular diseases. 13…”
Section: Introductionmentioning
confidence: 99%
“…Metabolic syndrome (MetS), characterized by decreased glucose tolerance and increased insulin resistance, is gaining importance due to increased prevalence and earlier presentation in the HIV-positive population, predisposing them to cardiovascular diseases. [1][2][3] Prevalence of MetS in HIV ranges from 7% to 45%. 4,5 Among Latin American PLWH receiving ART, it has been reported up to 20.2%.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations